2015
DOI: 10.1111/jphp.12368
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasites of medical and veterinary importance: drug resistance and the need for alternative control methods

Abstract: Objectives Despite multiple attempts at eradication, many ectoparasites of humans and domestic livestock remain a persistent problem in the modern world. For many years, a range of pesticide drugs including organophosphates, organochlorides and synthetic pyrethroids provided effective control of these parasites; but intensive use of these drugs has led to the evolution of resistance in many target species. This paper aims to review the effectiveness of current control methods and discuss potential alternatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 129 publications
(253 reference statements)
0
58
0
4
Order By: Relevance
“…In this context, research on tick vaccine development is more advanced than that reported for other major ectoparasites. Therefore, tick vaccine research may provide models for development of vaccines against other arthropod pests [20,83,[85][86][87][88]. In this direction, recent efforts using tick Subolesin or the Akirin homolog in mosquitoes have shown how vaccination with these antigens protects against multiple ectoparasites and the infection with vector-borne pathogens [42,43,89] (BOX 1).…”
Section: Tick Vaccines and The Development Of Vaccines Against Other Mamentioning
confidence: 99%
“…In this context, research on tick vaccine development is more advanced than that reported for other major ectoparasites. Therefore, tick vaccine research may provide models for development of vaccines against other arthropod pests [20,83,[85][86][87][88]. In this direction, recent efforts using tick Subolesin or the Akirin homolog in mosquitoes have shown how vaccination with these antigens protects against multiple ectoparasites and the infection with vector-borne pathogens [42,43,89] (BOX 1).…”
Section: Tick Vaccines and The Development Of Vaccines Against Other Mamentioning
confidence: 99%
“…). The use of chemotherapeutants in aquaculture creates a strong selection pressure, and the fast generation time of parasites and pathogens allows for rapid adaptation to treatments (Boots ; McNair ). The use of chemotherapeutants to limit and combat disease and parasites is, thus, unlikely to remain effective in areas where genetic resistance can penetrate the population quickly (e.g.…”
Section: The Common Toolbox For Treating Parasites (And Why It Does Nmentioning
confidence: 99%
“…For example, at least 10 species of gastrointestinal nematodes associated with cattle have evolved resistance to antihelmintic drugs [35] and numerous ectoparasitic arthropods affecting cattle, sheep, poultry and farm-raised salmon have evolved resistance to insecticides and acaricides [43]. In addition, the widespread use of antimicrobials in both livestock and crop production has led to the evolution of resistance in numerous disease agents [39,40].…”
Section: (B) Adaptation To Agricultural Practicesmentioning
confidence: 99%